Prospects for the Myanmar rubber sector: An analysis of the viability of smallholder production in Mon state - van Asselt, Joanna; Htoo, Kyan; Dorosh, Paul A.; International Food Policy Research Institute; Center for Economic Development (Michigan State University, 2018)
In this paper we examine the profitability of smallholder rubber production in Mon State utilizing data from the Mon State Rural Household Survey (MSRHS) conducted from May to June 2015. This paper also draws on qualitative data collected from rubber producer focus groups in Mon, as well as other interviews with rubber producers, traders, and processors. We use this primary data on smallholder production in Mon State to estimate stallholder production costs and the profitability of smallholder rubber production across alternative yield and price scenarios.